2019
DOI: 10.1016/j.laa.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Perfect state transfer on abelian Cayley graphs

Abstract: Perfect state transfer (PST) has great significance due to its applications in quantum information processing and quantum computation. In this paper we present a characterization on connected simple Cayley graph Γ = Cay(G, S) having PST. We show that many previous results on periodicity and existence of PST of circulant graphs (where the underlying group G is cyclic) and cubelike graphs (G = (F n 2 , +)) can be derived or generalized to arbitrary abelian case in unified and more simple ways from our characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…The phenomenon of perfect state transfer (PST) in quantum communication networks was originally introduced by Bose in [14]. This work has attracted much research interest since many applications have been found in quantum information processing and cryptography (see [1,2,3,5,11,15,17,18,34,38,37] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of perfect state transfer (PST) in quantum communication networks was originally introduced by Bose in [14]. This work has attracted much research interest since many applications have been found in quantum information processing and cryptography (see [1,2,3,5,11,15,17,18,34,38,37] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…We also remark that Cayley graphs of the group Z n 2 , known as cubelike graphs, have received much attention previously [6,15]. As the quotient of an extraspecial group of order 2 2n+1 by its center of order 2 is isomorphic to Z 2n 2 , it is interesting to compare the quantum walks on these groups.…”
Section: Discussionmentioning
confidence: 98%
“…Bernasconi et al and Cheung et al studied perfect state transfer in cubelike graphs [3,6]. Tan et al generalized this work by studying Cayley graphs of arbitrary abelian groups in [15], and provided conditions for perfect state transfer in terms of the spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…We extend Theorem 2.4 of [22] to (Laplacian) fractional revival here. (1) The eigenvalues of L(G) are integers;…”
Section: Continuous-time Quantum Walksmentioning
confidence: 97%